"We don't kiss like that": Inuit women respond to music video representations. (June 2018) - Glennie, Cassidy
This study provides sociological insight into the response of Inuit women to mainstream Western media representations of their culture. Historically, there have been inaccurate and stereotypical media representations of Indigenous peoples reproduced in many forms of entertainment media. Social theories such as Pierre Bourdieu's symbolic violence, Johan Galtung's cultural violence, and George Gerbner and Gaye Tuchman's symbolic annihilation are applied to contemporary media representations of Inuit women. This study explains how Inuit women make sense of popular music videos that utilize Inuit themes. Local Indigenous organizations in Rankin Inlet, Nunavut, were collaborated with to facilitate focus groups for Inuit women to express their reactions to the videos and discuss how their culture is presented in mainstream Western music videos. Key themes that were identified include the following: unrealistic Western beauty standards projected onto Indigenous women; the normalization of harmful media tropes including the silence regarding Inuit women's victimization, and the issue of missing and murdered aboriginal women; and the importance of positive role models, and self-representation of Inuit women in media.